Factors affecting state railway of Thailand (SRT) passenger train service use decision: A structural equation model - Chalermsap Lieophairot; Nuttawut Rojniruttikul (My University, 2023)
The State Railway of Thailand's (SRT) rail passenger ridership has dropped from a peak of 88 million rides in 1994 to less than 23 million in 2022, with the reasons for this collapse being numerous. Therefore, the authors set out to examine how organizational image (OI), service quality (SQ), service motivation (SM), and service satisfaction (SS) affect SRT use decision (SUD) making. From August-October 2022, multiple-stage random sampling was used to select a sample of 1,250 SRT passengers from five regional rail lines and their associated 25 stations. A confirmatory factor analysis goodness-of-fit was used to confirm the model's fit. A structural equation model (SEM) using LISREL 9.10 was then used to analyze the ten hypothesized relationships. The quantitative research used a 5-level questionnaire to measure the study's five constructs and 22 observed variables. The reliability of the items ranged from 0.86 to 0.93. The data analysis included calculating various statistical measures. Results showed that the model's causal variables positively affected passenger SRT use decision, with an R2 of 71%. When ranked by total effect (TE) values, service quality (SQ = 0.89) was viewed by the surveyed passengers as most important, followed by service satisfaction (SS = 0.67), organizational image (OI = 0.63), and service motivation (SM = 0.53). Additionally, all ten hypotheses were supported, with service satisfaction judged the most essential to SRT Use Decisions. The study's novelty is the ever-growing requirement for the SRT to serve as a regional hub in a more extensive East Asian rail and infrastructure strategy. The paper contributes significantly to the academic literature on factors affecting rail transportation use intent.
Keywords: LISREL; Goodness of fit; Sample (material); Customer Satisfaction; Customer Service Quality and Loyalty